Evidence available for patient-identified priorities in depression research: results of 11 rapid responses. Issue 6 (28th June 2019) - Sebastianski, Meghan; Gates, Michelle; Gates, Allison; Nuspl, Megan; Bialy, Liza M; Featherstone, Robin M; Breault, Lorraine; Mason-Lai, Ping; Hartling, Lisa
Abstract : Objectives: Patient priority setting projects (PPSPs) can reduce research agenda bias. A key element of PPSPs is a review of available literature to determine if the proposed research priorities have been addressed, identify research gaps, recognise opportunities for knowledge translation (KT) and avoid duplication of research efforts. We conducted rapid responses for 11 patient-identified priorities in depression to provide a map of the existing evidence. Design: Eleven rapid responses. Data sources: Single electronic database (PubMed). Eligibility criteria: Each rapid response had unique eligibility criteria. For study designs, we used a stepwise inclusion process that started with systematic reviews (SRs) if available, then randomised controlled trials and observational studies as necessary. Results: For all but one of the rapid responses we identified existing SRs (median 7 SRs per rapid response, range 0–179). There were questions where extensive evidence exists (ie, hundreds of primary studies), yet uncertainties remain. For example, there is evidence supporting the effectiveness of many non-pharmacological interventions (including psychological interventions and exercise) to reduce depressive symptoms. However, targeted research is needed that addresses comparative effectiveness of promising interventions, specific populations of interest (eg, children, minority groups) and adverse effects. Conclusions: We identified an extensive body of evidence addressing patient priorities in depression and mapped the results and limitations of existing evidence, areas of uncertainty and general directions for future research. This work can serve as a solid foundation to guide future research in depression and KT activities. Integrated knowledge syntheses bring value to the PPSP process; however, the role of knowledge synthesis in PPSPs and methodological approaches are not well defined at present.